Blind estimation of MPSK carrier frequency - DENG Zhen-miao; LIU Yu (Tongxin xuebao)
The blind carrier frequency estimation of multi-phase shift keying（MPSK） signals was discussed.The carrier frequency was coarsely estimated without the prior knowledge of received signals.Consequently the signals were trans-formed to the baseband-modulated PSK signals by correlation to estimate the symbol rate.With the estimations of the carrier frequency and the symbol rate,the problem of carrier frequency estimation was converted to that of frequency offset.Because the phase of baseband-modulated PSK signal is a piecewise linear function and the slope coefficient of every segment is a linear function of frequency offset,the multi-segment line can be transformed to a straight-line and then the least squares fitting method was applied to estimate the slope coefficient.The simulation results show that this method can accurately estimate the carrier frequency without the prior knowledge.